Gender as a Moderator of Cognitive and Affective Outcome After Traumatic Brain Injury - Rodger Wood (The Journal of Neuropsychiatry and Clinical Neurosciences, 2009)
The aim of this investigation was to compare cognitive and affective functions in men and women who had suffered comparable brain injuries. In a prospective matched cohort design, 150 community- dwelling patients were individually matched on the basis of age, severity of injury, premorbid IQ, and time since injury. Women were significantly more impaired in verbal and visual memorycompared with men. The degree of cognitive decline was significantly positively correlated with age in women, but not in men. Women had marginally higher scores compared with men on measures of anxiety and depression. It is concluded that gender is a moderator of cognitive and affective outcome after brain injury.